Friendship intimacy in early and late Filipino adolescents - Dy, M. R. (Compendium of Human Ecology Researches in the Philippines, 2003)
This study explored friendship intimacy in early and late adolescence. There were 405 respondents from Los Banos, Laguna aged 12-21 years old with nearly equal numbers of males and females. Each respondent was administered a survey schedule and the Friendship Intimacy Scale. The findings of the study showed that characteristics of early and late adolescent friendships in terms of formation , composition, activities, extent of self-disclosure, and the expressions of affection. Age was not significant factor in friendship intimacy. Early and late adolescent mean scores on the friendship intimacy. Early and late adolescent mean scores on the friendship intimacy scale were not significantly different. On the other hand, gender was a significant factor with the female adolescents manifesting this more than the males. Further studies on a wider group of children and adolescents can enrich the understanding and importance of friendship intimacy to socio-emotional development in the Philippine setting.